Freeze-thaw stability of frozen dough containing superheated steam-treated wheat flour: insights into gluten protein aggregation, structural interactions, and network integrity - Xuepan Qi; Ying Wang; Chang Han; Yamei Jin; Dan Xu; Fengfeng Wu; Qiyan Zhao; Xueming Xu (Food Hydrocolloids, 2026)

Electronegativity-guided d-band center tuning of MnFeCoNiCu high-entropy alloy: Boosting polysulfide conversion for high-performance lithium-sulfur batteries - Jingkun Ren; Yu Shao; Xitian Zhang; Fengfeng Han; Di Wang; Qi Jin; Tong Qi; Zhihao Liu; Jing He; Xinzhi Ma; Lili Wu (Chemical Engineering Journal, 2026)

Integrated study in zebrafish elucidates the pivotal role of ribosomal and metabolic crisis in propiconazole-induced neurotoxicity - Xinliang Zhu; Xuanfang Long; Peijing Li; Xumin He; Shuilian Qi; Linyi Han; Yingzhu Sang; Xinyu Zhu; Fengfeng Lei (Chemico-Biological Interactions, 2026)

Contributions of superheated steam-treated gluten and starch to the freeze-thaw stability of frozen dough: Evidence from component-reconstituted substitution systems - Xuepan Qi; Ying Wang; Chang Han; Yamei Jin; Dan Xu; Fengfeng Wu; Huang Zhang; Xueming Xu (Food Bioscience, 2026)

Freeze-thaw stability of frozen dough containing superheated steam-treated wheat flour: Evidence from water states and starch properties - Xuepan Qi; Chang Han; Ying Wang; Yamei Jin; Dan Xu; Fengfeng Wu; Xueming Xu (Food Hydrocolloids, 2026)

Synergistic catalytic mechanism of constituent metal atoms in high−entropy alloy catalysts for Li − S batteries - Tong Qi; Yu Shao; Chi Zhang; Di Wang; Fengfeng Han; Qi Jin; Zhihao Liu; Xitian Zhang; Lu Li; Lili Wu (Chemical Engineering Journal, 2026)

Superheated steam-treated wheat flour for the preparation of low-fat short dough biscuits: Effects on dough characteristics and biscuit quality - Chang Han; Xuepan Qi; Yamei Jin; Na Yang; Dan Xu; Fengfeng Wu; Xueming Xu (Food Hydrocolloids, 2026)

Superheated steam-treated wheat flour: A novel approach to improve freeze-thaw stability of frozen raw noodles - Xuepan Qi; Chang Han; Ying Wang; Yamei Jin; Dan Xu; Fengfeng Wu; Xueming Xu (Innovative Food Science & Emerging Technologies, 2025)

Understanding sustainability of woody species suitability zones on the Loess Plateau for optimal creation zone selection in response to future climate change - Haihong Qiu; Hairong Han; Xiaoqin Cheng; Fengfeng Kang (Journal of Environmental Management, 2025)

Potential oscillation enhanced lithium ion pump membrane for lithium ion extraction - Guojun Han; Wenbiao Ma; Zhi Wang; Xiaowei An; Fengfeng Gao; Xiao Du; Zhong Liu; Guoqing Guan; Xiaogang Hao (Journal of Environmental Chemical Engineering, 2024)

PI3K/AKT/FOXO3a Pathway Induces Muscle Atrophy by Ubiquitin-Proteasome System and Autophagy System in COPD Rat Model - Haiyang Yu; Guiyin Zhu; Dongmei Wang; Xuan Huang; Fengfeng Han (Cell Biochemistry and Biophysics, 2024)

Coupling strength of human-natural systems mediates the response of ecosystem services to land use change - Baoan Hu; Zuzheng Li; Huifeng Wu; Hairong Han; Xiaoqin Cheng; Fengfeng Kang (Journal of Environmental Management, 2023)

Effects of Betula platyphylla invasion in North China on soil aggregate stability, soil organic carbon and active carbon composition of larch plantation - Ying Ma; Huifeng Wu; Baoan Hu; Xiaoqin Cheng; Fengfeng Kang; Hairong Han (Plant and Soil, 2023)

Mixed plantation regulates forest floor water retention and temperature sensitivity in restored ecosystems on the Loess Plateau, China - Huifeng Wu; Baoan Hu; Jiaxing Yan; Xiaoqin Cheng; Penghui Yi; Fengfeng Kang; Hairong Han (CATENA, 2023)

Dramatic shift in the drivers of ecosystem service trade-offs across an aridity gradient: Evidence from China's Loess Plateau - Baoan Hu; Huifeng Wu; Hairong Han; Xiaoqin Cheng; Fengfeng Kang (Science of The Total Environment, 2023)

Aridification weakens ecosystem services by reducing complexity and stability of socio-ecological networks - Baoan Hu; Huifeng Wu; Zuzheng Li; Hongyuan Jing; Zixiao Zheng; Hairong Han; Xiaoqin Cheng; Fengfeng Kang (Journal of Cleaner Production, 2023)

Serum Iron and Ferritin Levels Are Correlated with Complement C3 - Shuang Wen; Yeqin Sha; Yinling Li; Zhilian Rui; Chenhong Si; Yuning Zhou; Fengfeng Yan; Bicheng Wang; Jingming Hu; Xu Han; Dongyan Shi (Biological Trace Element Research, 2021)

Genetic properties and pathogenicity of a novel reassortant H10N5 influenza virus from wild birds - Yane Jia; Jiayun Yang; Zhengxiang Wang; Yingying Du; Jie Cui; Liang Wang; Fengfeng Guo; Maijuan Yang; Shufang Han; Qiyun Zhu (Archives of Virology, 2017)

Combination of intratypic and intertypic recombinant events in EV71: a novel evidence for the “triple-recombinant” strains of genotype A viruses in Mainland China from 2008 to 2010 - Yongjuan Liu; Fengfeng Zhang; Chong Fu; Suying Wu; Xiong Chen; Yingying Shi; Bingfei Zhou; Lianglu Zhang; Yingying Zhang; Song Han; Jun Yin; Biwen Peng; et al. (Virus Genes, 2015)

FluG affects secretion in colonies of Aspergillus niger - Fengfeng Wang; Pauline Krijgsheld; Marc Hulsman; Charissa de Bekker; Wally H. Müller; Marcel Reinders; Ronald P. de Vries; Han A. B. Wösten (Antonie van Leeuwenhoek, 2015)

VeA of Aspergillus niger increases spore dispersing capacity by impacting conidiophore architecture - Fengfeng Wang; Jan Dijksterhuis; Timon Wyatt; Han A. B. Wösten; Robert-Jan Bleichrodt (Antonie van Leeuwenhoek, 2015)

A novel finding for enterovirus virulence from the capsid protein VP1 of EV71 circulating in mainland China - Yongjuan Liu; Chong Fu; Suying Wu; Xiong Chen; Yingying Shi; Bingfei Zhou; Lianglu Zhang; Fengfeng Zhang; Zhihao Wang; Yingying Zhang; Chengpeng Fan; Song Han; et al. (Virus Genes, 2014)

Short-term effects of thinning on soil respiration in a pine (Pinus tabulaeformis) plantation - Xiaoqin Cheng; Hairong Han; Fengfeng Kang; Ke Liu; Yali Song; Bin Zhou; Yong Li (Biology and Fertility of Soils, 2014)

An efficient gene deletion procedure for the mushroom-forming basidiomycete Schizophyllum commune - Robin A. Ohm; Jan F. de Jong; Elsa Berends; Fengfeng Wang; Han A. B. Wösten; Luis G. Lugones (World Journal of Microbiology and Biotechnology, 2010)

The septal pore cap is an organelle that functions in vegetative growth and mushroom formation of the wood‐rot fungus Schizophyllum commune - Arend F. Van Peer; Fengfeng Wang; Kenneth G. A. Van Driel; Jan F. De Jong; Elly G. Van Donselaar; Wally H. Müller; Teun Boekhout; Luis G. Lugones; Han A. B. Wösten (Environmental Microbiology, 2010)
Summary Mushroom‐forming basidiomycetes colonize large areas in nature. Their hyphae are compartmentalized by perforated septa, which are usually covered by a septal pore cap (SPC). Here, we describe, for the first time, the composition and function of SPCs using the model system Schizophyllum commune . The SPC of S. commune was shown to consist of a proteinaceous matrix covered by a lipid membrane. The matrix was demonstrated to define the ultrastructure of the SPC and to consist of two main proteins, Spc14 and Spc33. Gene spc14 encodes a protein of 86 amino acids, which lacks known domain, signal or localization sequences. Gene spc33 encodes a 239 and a 340 amino acid variant. Both forms contain a predicted signal anchor that targets them to the ER. Immuno‐localization showed the presence of Spc33 in the SPC but not in ER. From this and previous reports it is concluded that the SPC is derived from this organelle. Inactivation of spc33 resulted in loss of SPCs and the inability to close septa. The latter may well explain why vegetative growth and mushroom formation were severely reduced in strains in which spc33 was inactivated.